2010
DOI: 10.1111/j.1475-6811.2010.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of romantic relationship formation: Attachment style, prior relationships, and dating goals

Abstract: This prospective study (N = 90) investigated the early formation of romantic relationships within an attachment‐theoretical framework. Specifically, it tested whether general attachment to romantic partners was predictive of single individuals' progressing from not dating to dating and from not dating or casual dating to a committed and exclusive relationship when simultaneously considering desire for starting a committed relationship, prior dating involvement, and self‐perceived physical attractiveness. Attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 22 publications
4
60
0
1
Order By: Relevance
“…This finding is consistent with at least two studies that failed to find changes in attachment avoidance after a security-focused manipulation (Carnelley & Rowe, 2007;Lavi, 2007). Schindler, Fagundes, and Murdock (2010) suggest that those who are avoidantly attached tend to be more hesitant to form a committed relationship with a partner than secure or anxiously attached individuals. In our sample, it is possible that, unlike for anxious attachment, avoidant attachment schemas were not effectively activated by the virtual relationship-building program or the representational priming procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with at least two studies that failed to find changes in attachment avoidance after a security-focused manipulation (Carnelley & Rowe, 2007;Lavi, 2007). Schindler, Fagundes, and Murdock (2010) suggest that those who are avoidantly attached tend to be more hesitant to form a committed relationship with a partner than secure or anxiously attached individuals. In our sample, it is possible that, unlike for anxious attachment, avoidant attachment schemas were not effectively activated by the virtual relationship-building program or the representational priming procedure.…”
Section: Discussionmentioning
confidence: 99%
“…One indicator of willingness to commit to a relationship partner is levels of attachment. Schindler et al () found that those who reported greater attachment avoidance were less likely to commit to a relationship. This may be because those who are higher in attachment avoidance report being less ready to commit to a romantic partner (Hadden et al, ).…”
Section: Romantic Relationships and Sexual Activity In Adolescence Anmentioning
confidence: 99%
“…Over the past decades, attachment theory has become one of the major frameworks for the study of romantic relationships (Schindler et al 2010). It provides a perspective for understanding individual differences in the degree to which people are comfortable with intimacy (Fraley and Shaver 2000).…”
Section: Introductionmentioning
confidence: 99%